GREEN HUMAN RESOURCE MANAGEMENT PRACTICES AMONG GOVERNMENT AIDED TEACHING FACULTIES (International Journal of Food and Nutritional Sciences, 2022)
"Green HRM" refers to the application of human resource management policies to encourage the efficient use of resources inside businesses and, more broadly, to promote environmental sustainability. In today's society, green HRM is a relatively new notion. Green human resource management processes are primarily utilized to lower each faculty's carbon footprint. It also aids in persuading faculty to care for resources and participate in waste management in order to reduce pollution. GHRM is concerned with human resource operations that are environmentally friendly and encourage the organization's utilization of natural resources in a sustainable manner. Some GHRM actions have become standard in recent years, such as minimizing needless printing, recycling printed materials, using telephone or video interviewing and conferences to reduce travel's environmental impact, and so on. To analyse the Perception of teaching faculty regarding implementation of Green HRM practices in government aided colleges. The study will try to emphasize the college's current green HRM practices, as well as the scope and effects of such practices at a government aided college, and will suggest additional initiatives we might take in this area. The research is based on primary data collected through a questionnaire issued to government aided college faculty. Systematic sampling method has been used in this study and sampling size on (n=91) is taken. This research is based on perception of green human resource management practices among the teaching faculties of government aided arts and science college.